Upaya Pengembangan Kemandirian Dan Motorik Halus Anak Melalui Kegiatan Dressing Frame Educative Pada Kelompok B Di Raudhatul Athfal An Najiha Bedaro Muko-Muko Bathin VII Bungo - Rosnida; M.Muzakki; Wiwin Narti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research is motivated by the low independence and fine motor skills of group B children at RA An Najiha Bedaro Muko-Muko Bathin VII Bungo, which can be seen from the fact that there are still many children who need the help of teachers in simple dress activities. This condition shows that the learning that takes place has not fully provided concrete, active, and in accordance with the characteristics of early childhood. This study aims to analyze efforts to develop children's independence and fine motor skills through educational dressing frame activities. The method used is classroom action research with the Kemmis and McTaggart models which is carried out in two cycles through the stages of planning, implementation, observation, and reflection. The research subjects amounted to 20 children of group B. Data were collected through observation, interviews, documentation, and performance tests, then analyzed qualitatively and quantitatively. The results of the study showed that educational dressing frame activities were able to increase children's involvement, courage to try, responsibility in completing tasks, and finger, hand, and eye coordination skills. Thus, it can be concluded that the educational dressing frame is effectively used as a learning medium to increase the independence and fine motor skills of early childhood gradually, measurably, and in a contextual manner.